Forest communities in old manor parks as emerald network elements of European Russia - Gaivoronskaya A.A.; Avramenko M.V.; Moskalenko I.V.; Nozdracheva E.V.; Chigrai O.N.; Chuchin D.I. (BIO Web of Conferences)
The conservation value of the territories is clearly demonstrated by the Emerald Network criteria and the EUNIS habitat classification. These tools diagnose the conservation value of the territories by taking into account their ecosystem functions. The research goal was fulfilled thanks to the well-developed syntaxonomy of vegetation and clear formulations for describing the diagnostic features of plant communities formed in the synecological optimum of habitats. The inventory work in old manor parks of the Bryansk region justified objects with unique habitats for inclusion in the Emerald Book of Russia. Our survey of 15 old manor parks in the Bryansk region revealed seven complexes where zonal plant communities are formed. These habitats are of great natural, cultural, and historical significance and should be designated as "key habitats." The plant communities of Querco-Tilion and Alnion glutinosae in the manor parks with different stages of demutational shiftsDunin-Borkovskiy, Rumyantsev, Ryovny, Foevichi, Lyalichi, Koretsky, and Lubin Khutor manors have been classified as habitats of G1 categories. 22 - Mixed oak- elm-ashtree forests; G1.A1 - Northern Central Russian oak-lime forests; G1.A4 - Gully and slope forests. The following habitat codes were determined according to the EUNIS system, which complements the classification of the ecological network area types: T1: Eastern European black alder swamp forests; T1-E: Northern Middle Russian oak-lime forests, sub-taiga lime forests. To preserve unique habitats and formed communities, park complexes must be designated as regional natural monuments. This will ensure they are included in the relevant legislation and regulations. Estate parks must also be incorporated into the ecological framework for Bryansk and neighboring regions. Finally, the introduction of invasive plants that disrupt homeostatic regulation mechanisms must be controlled.